2012
DOI: 10.3109/0886022x.2011.643364
|View full text |Cite
|
Sign up to set email alerts
|

Association of PAX2 with Cell Apoptosis in Unilateral Ureteral Obstruction Rats

Abstract: Renal interstitial fibrosis (RIF) is the final common pathway for chronic kidney disease. Cell apoptosis is a critical detrimental event that leads to renal fibrosis. Paired box 2 (PAX2) plays a major role in the development of the kidney. This study was performed to investigate whether PAX2 was associated with cell apoptosis in the progression of RIF in unilateral ureteral obstruction (UUO) rats. Eighty Wistar male rats were divided into two groups randomly: sham operation group (SHO) and model group subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…We found a large number of apoptotic ureteral epithelial cells in the VUR group, and no apoptotic ureteral epithelial cells were found in the control group. Pax2 expression was correlated with ureteral epithelial cell apoptosis in the VUR group, consistent with the results found in unilateral ureteral obstruction rats by Zhou et al [35]. During the transformation of mesenchymal cells to epithelial cells, signs of apoptosis such as karyopycnosis and karyorrhexis can be found around the newly formed epithelial cells [27].…”
Section: Discussionsupporting
confidence: 89%
“…We found a large number of apoptotic ureteral epithelial cells in the VUR group, and no apoptotic ureteral epithelial cells were found in the control group. Pax2 expression was correlated with ureteral epithelial cell apoptosis in the VUR group, consistent with the results found in unilateral ureteral obstruction rats by Zhou et al [35]. During the transformation of mesenchymal cells to epithelial cells, signs of apoptosis such as karyopycnosis and karyorrhexis can be found around the newly formed epithelial cells [27].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that the expressions of TGF-βl, Col-IV and FN in the renal interstitium of the GU group were increased compared to those in the renal interstitium of the SHO group. The results in this study were similar with those in our previous report [21]. It indicated that the RIF model in our study was established successfully.…”
Section: Discussionsupporting
confidence: 92%
“…The average threshold cycle (Ct, the cycles of template amplification to the threshold) was worked out as the value of each sample. The data of fold of changes was analyzed using 2 −ΔΔCt [38,39]. For example, the ΔΔCt of prohibitin mRNA expression in UUO group in 14-day was as follow: ΔΔCt prohibitin,14-day,UUO group = (Ct prohibitin, 14-day, UUO group − Ct β-actin, 14-day, UUO group ) − (Ct prohibitin, 14-day, SHO group − Ct β-actin, 14-day, SHO group ), and the fold of changes of prohibitin mRNA expression in the UUO group in 14-days was 2 −ΔΔCt prohibitin, 14-day, UUO group .…”
Section: Methodsmentioning
confidence: 99%